Illness as journey: narrative medicine in the patient quest - Correia, Alda (Cadernos de Literatura Comparada, 2014)
In her book Illness as Metaphor (1978) Susan Sontag writes that “everyone who is born holds dual citizenship, in the kingdom of the well and in the kingdom of the sick. Although we all prefer to use only the good passport, sooner or later each of us is obliged, at least for a spell, to identify ourselves as citizens of that other place”. Illness is therefore a kind of travel into another space and kingdom and it can be felt as a frightening journey. The stages of the archetypal hero quest journey can be perceived in the patient evolution, namely their reflexive quality. Narrative medicine can enable the patient to take over the reins of this journey, to look at himself and re-evaluate every moment of existence, to reconsider the steps of the way in a relatively distanced and self analysing attitude. This paper will show how the patient evolution can be interpreted as a journey quest and how narrative medicine can support this purpose.